2019
DOI: 10.1177/1758835919866964
|View full text |Cite
|
Sign up to set email alerts
|

High blood sugar levels but not diabetes mellitus significantly enhance oxaliplatin chemoresistance in patients with stage III colorectal cancer receiving adjuvant FOLFOX6 chemotherapy

Abstract: Background: The high prevalence of type 2 diabetes mellitus (DM) among patients with colorectal cancer (CRC) is becoming a serious public health concern worldwide. FOLFOX4 chemotherapy is one of the most widely used adjuvant therapies in patients with stage III colon cancer after surgical resection. However, chemotherapy resistance is associated with a poor prognosis. The prognostic impact of high blood sugar levels on oxaliplatin resistance in CRC patients is an unexplored topic. Methods: In total, 157 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
2
29
0
1
Order By: Relevance
“…This is well supported by previous studies who have found the same effect when using resazurin 47,48 . The sensitivity of cancer cells to drug treatments in different glucose concentrations is not only relevant for in vitro testing, but also clinically where many patients may present with T2D and elevated blood glucose levels, which has been associated with chemoresistance 49 . Not all cancer cells exhibit Warburg metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This is well supported by previous studies who have found the same effect when using resazurin 47,48 . The sensitivity of cancer cells to drug treatments in different glucose concentrations is not only relevant for in vitro testing, but also clinically where many patients may present with T2D and elevated blood glucose levels, which has been associated with chemoresistance 49 . Not all cancer cells exhibit Warburg metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GC cells tend to show multidrug resistance and reduced susceptibility to chemotherapy drugs under high glucose conditions [27]. Another study reported that hyperglycemia can enhance oxaliplatin chemoresistance and lead to poor clinical outcomes in stage III colorectal cancer patients receiving adjuvant chemotherapy [28]. This study aimed to investigate the effects of hyperglycemia on the GC malignant phenotype and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report to demonstrate that blood glucose levels are related to the prognosis of cancer patients on a ketogenic diet. Only one previous report was found in patients with stage III colorectal cancer receiving adjuvant FOLFOX6 [24]. The ketogenic diet is said to affect glucose metabolism [25] and gene expression [26,27] because of changes in the metabolic environment and ketone bodies acting as signal molecules [28].…”
Section: Discussionmentioning
confidence: 99%